Tetracyclines modulate cytosolic Ca2+ responses in the osteoclast associated with "Ca2+ receptor" activation. Issue 3 (June 1993) - Bax, Christopher M. R.; Shankar, Vijai S.; Towhidul Alam, A. S. M.; Bax, Bridget E.; Moonga, Baljit S.; Huang, Christopher L.-H.; Zaidi, Mone; Rifkin, Barry R.
Abstract : We report the effects of tetracycline analogues on cytosolic Ca 2+ transients resulting from application of ionic nickel (Ni 2+ ), a potent surrogate agonist of the osteoclast Ca 2+ "receptor". Preincubation with minocycline (1 mg/l) or a chemically modified tetracycline, 4-dedimethyl-aminotetracycline (CMT-1) (1 or 10 mg/l), resulted in a significant attenuation of the magnitude of the cytosolic [Ca 2+ ] response to an application of 5 mM-[Ni 2+ ]. Preincubation with doxycycline (1 or 10 mg/l) failed to produce similar results. In addition, application of minocycline alone (0.1–100 mg/l) resulted in a 3.5-fold elevation of cytosolic [Ca 2+ ]. The results suggest a novel action of tetracyclines on the osteoclast Ca 2+ "receptor".